Employee Performance Impact on Communication and Work Environment - Novita Wahyu Setyawati; Clara Agustina; Dewi Sri Woelandari PG (PT FORMOSA CENDEKIA GLOBAL, 2023)
In a human resource company, it is important for the company, to advance the company and improve employee performance properly. Performance can be influenced by good communication between superiors and subordinates, a good work environment. Performance is an achievement of results by employees in carrying out a job task and responsibility when employees are able to work optimally. If effective communication is established directly or indirectly, then employees will feel comfortable in the work environment, the more employees are given comfort and good communication to foster, the employees will work optimally in carrying out their duties. Based on the test results that have been carried out on communication and the Work Environment on Employee Performance, it can be explained through the discussion as follows Communication has a positive and significant effect on employee performance, work environment has a positive and significant effect on employee performance, and communication and work environment have a positive and significant effect on employee performance.